Considering the effects of mothers' economic resources on their children's physical and psychological health - Jaewon Lee; Jennifer Allen (Archives of Community Medicine and Public Health - Peertechz Publications, 2021)
There is a large body of studies examining parents' economic influences on their children's physical and psychological health [1-3]. However, few studies have addressed the impact of mothers' economic resources on health outcomes specifically [5-7]. Additionally, women's labor force participation is increasingly growing [7-9] and their roles in the workplace have a great impact on the labor market [10,11]. Thus, it is necessary to consider the influence of mothers' economic resources on their children's development, particularly regarding their physical and psychological health.